(untitled) (Global Journal of Human-Social Science, 2024)
Introduction This article proposes a comprehensive systematic review to analyze the potential of Clitoria guianensis as an anti-inflammatory and wound healing agent The emphasis on diversifying research methods aims to deepen understanding of its medicinal properties especially in the context of anti-inflammatory and wound healing activities The plant belonging to the genus Clitoria and native to Brazil is recognized for its aphrodisiac properties and is used as a sexual stimulant tonic and energizer Studies highlight the presence of bioactive compounds such as isoflavones which contribute to its medicinal properties Methodology The study was based on the Systematic Literature Review Protocol SLRP establishing a framework for comprehensively reviewing scientific literature The objective was to identify the medicinal properties of C guianensis in Brazil focusing on its potential anti-inflammatory and wound healing properties Results The results of this scientific review aim to substantiate the consideration of C guianensis as a potentially beneficial plant in tissue regeneration processes Although not directly addressing wound healing it is suggested that its antiinflammatory properties and modulation of the immune response may positively influence these processes Discussion Systematic analysis provides a critical and comprehensive insight into the medicinal properties of C guianensis contributing to the understanding of its antiinflammatory and wound healing potential A diversified approach integrating in vivo in vitro and in silico data is essential for understanding its potential in clinical practice Conclusion This study by conducting a systematic review of scientific literature explored evidence related to the antiinflammatory and wound healing potential of C guianensis Practical implications confirm the medicinal and pharmacochemical properties of this medicinal plant revealing its chemical and therapeutic richness and highlighting the importance of further studies Thus this work establishes a solid foundation for future research advancing the understanding and therapeutic application of C guianensis in medicine